A review on the pattern of electricity generation and emission in Iran from 1967 to 2008 - Mazandarani, A.; Mahlia, T.M.I.; Chong, W.T.; Moghavvemi, Mahmoud (Elsevier, 2010)
The electricity consumption growth in Iran requires a rapid development of power plant construction. Like many other countries, most of the power plants in Iran are using fossil fuel. In the past decade, thermal power plants generated about 94% of electricity and about 6% was generated by renewable sources such as hydro-power. This study is to show a clear view of 42 years an evolutionary trend of Iran's electricity generation industry. The capacity of power generation installed and electricity generation from the years 1967 to 2008 has been gathered. The total pollutant emissions and emission per unit electricity generation for each type of power plants have also been calculated using emission factors and the pattern of electricity generation and emission has been presented. The results shown that encouraging of using renewable energy sources and increasing the contribution of the combined cycle as a best type of thermal power plants and use more natural gas is recommended to reduce emission.